Optimización del tratamiento de aguas residuales de cultivos de flores usando humedales construidos de flujo subsuperficial horizontal (2016)
ABSTRACT: To optimize the wastewater treatment system of flower crops in order to improve pollutant removal efficiency, using a horizontal subsurface flow constructed wetland. Methodology: An exploratory experimental study was conducted in two stages; in the first stage the treatment system was conditioned physically, chemically and biologically. In the second stage pollutant removal was monitored for nine months. To achieve this, chemical oxygen demand, biological oxygen demand, total solids, total suspended solids, pH and dissolved oxygen were monitored. Results: It was possible to improve the efficiency of the treatment system in 7.1% for biological oxygen demand, 4.1 % for chemical oxygen demand, 56.9 % for total solids and 117.2 % for total suspended solids. Conclusion: the concentration of COD decreased with the primary treatment (precipitation, chemical oxidation) and favored the efficiency of the secondary treatment system since the water to be treated had very high values of COD which may saturate the wetlands with persistent pollutants. Higher efficiency could be obtained by enhancing the primary treatment system.